IBM SMP NEGERI 4 DENPASAR - Arjaya, Ida Bagus Ari; Javandira, Cokorda (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2018)
SMP 4 Denpasar holds the title of